What question are we trying to answer? Embracing causal inference - Sargeant, Jan M.; O’Connor, Annette M.; Renter, David G.; Ruple, Audrey (Frontiers in Veterinary Science, 2024)
This manuscript summarizes a presentaEon given at the symposium for the Calvin Schwabe Award for LifeEme Achievement in Veterinary Epidemiology and PrevenEve Medicine, which was awarded to the first author. As epidemiologists, we are taught that "correlaEon does not imply causaEon". While true, idenEfying causes is a key objecEve for much of the research that we conduct. There is empirical evidence that veterinary epidemiologists are conducEng observaEonal research with the intent to idenEfy causes; many studies include control for confounding variables and causal language oden is used when interpreEng study results. Frameworks for studying causes include the arEculaEon of specific hypotheses to be tested, approaches for selecEon of variables, methods for staEsEcal esEmaEon of the relaEonship between the exposure and the outcome, and interpretaEon of that relaEonship as causal. When comparing observaEonal studies in veterinary populaEons to those conducted in human populaEons, the applicaEon of each of these steps differs substanEally. The a priori idenEficaEon of exposure-outcome pairs of interest is less common in observaEonal studies in the veterinary literature compared to the human literature, and prior knowledge is used to